Preparation method and application of nanoscale oxygen-doped nitrogen-rich carbon nitride

By introducing oxygen atom doping into nitrogen-rich carbon nitride and forming a nanoscale structure through ultrasonic exfoliation, the problem of low efficiency of photocatalysts was solved, and the effect of efficient production of hydrogen peroxide was achieved.

CN118598085BActive Publication Date: 2026-11-06JIANGSU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410680274.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-29
Publication Date
2026-11-06
Estimated Expiration
2044-05-29

AI Technical Summary

Technical Problem

Existing nitrogen-rich carbon nitride photocatalysts have low efficiency in the photocatalytic production of hydrogen peroxide, mainly due to their low specific surface area, insufficient visible light capture capacity, and rapid photoinduced recombination of electron-hole pairs.

Method used

By introducing oxygen atoms into nitrogen-rich carbon nitride and treating it under solution thermal conditions, combined with ultrasonic exfoliation, nanoscale oxygen-doped nitrogen-rich carbon nitride is formed, and its structural characteristics are adjusted to improve crystallinity and increase surface area.

Benefits of technology

It significantly improved photocatalytic performance, with hydrogen peroxide yield reaching 346.15 μmol/g. It exhibited good photocatalytic stability and charge transfer efficiency. The nanoscale oxygen-doped nitrogen-rich carbon nitride with a thickness of less than 2 nm showed excellent photocatalytic activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118598085B_ABST
    Figure CN118598085B_ABST
Patent Text Reader

Abstract

This invention discloses a method for preparing and applying nanoscale oxygen-doped nitrogen-rich carbon nitride. The method for preparing highly crystalline carbon nitride includes the following steps: S1: Calcination of 5-amino-1H-tetrazole in air atmosphere, followed by cooling, ball milling, washing, and drying to obtain nitrogen-rich carbon nitride; S2: Uniform mixing of nitrogen-rich carbon nitride and an acidic solution, followed by stirring and heating in an oil bath at a certain temperature, followed by cooling, washing, and drying to obtain oxygen-doped nitrogen-rich carbon nitride; S3: Uniform mixing of alcohol, deionized water, and oxygen-doped nitrogen-rich carbon nitride, followed by ultrasonic exfoliation at room temperature, washing, and drying to obtain nanoscale oxygen-doped nitrogen-rich carbon nitride. The nanoscale oxygen-doped nitrogen-rich carbon of this invention possesses small size, large surface area, and abundant active sites, exhibiting excellent photocatalytic performance, which is beneficial for the efficient photocatalytic production of hydrogen peroxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photocatalytic material preparation and application technology, and in particular to a nanoscale oxygen-doped nitrogen-rich carbon nitride, its preparation method and application. Background Technology

[0002] Hydrogen peroxide (H2O2) is a versatile and environmentally friendly oxidant that plays a crucial role in water treatment. It can be converted into highly oxidizing hydroxyl radicals, thus being widely used for disinfection and pollutant degradation. Compared to the traditional anthraquinone process for hydrogen peroxide synthesis, photocatalytic selective two-electron oxygen reduction (SCR) for H2O2 production offers unique advantages in terms of environmental sustainability. Therefore, photocatalysis is considered a promising method for sustainable H2O2 production. However, the main obstacle to its application lies in cost-effectiveness. The composition of the photocatalyst and the efficiency of the photonic chemical conversion process are two key factors affecting cost-effectiveness. Therefore, designing efficient and low-cost photocatalysts is a major challenge for achieving sustainable H2O2 production.

[0003] Nitrogen-rich carbon nitride (CN) has been widely used in various solar-driven chemical conversion reactions, such as water splitting, CO2 reduction, and organic chemical conversion reactions. Furthermore, the CN framework is particularly suitable for solar-powered hydrogen peroxide production due to the kinetic advantage of selective 2e-ORR at the carbon / nitrogen-based reaction center. However, the photocatalytic activity of CN is still limited by several unfavorable factors, resulting in low efficiency, including low specific surface area, insufficient visible light capture capacity, and rapid photoinduced electron-hole recombination. Nonmetals, however, possess high ionization energy and electronegativity, allowing them to form covalent bonds by gaining electrons when reacting with other compounds. Nitrogen-rich carbon nitride is a novel semiconductor with triazine and / or triazole units, exhibiting greater light absorption and excellent photocatalytic activity. Considering the above factors, photocatalytic performance is improved by introducing nonmetallic oxygen atoms into nitrogen-rich carbon nitride to reduce the band gap and enhance visible light absorption. Therefore, this invention is proposed. Summary of the Invention

[0004] To address the problems existing in the prior art, this invention proposes a method for preparing nanoscale oxygen-doped nitrogen-rich carbon nitride, comprising the following steps:

[0005] S1: 5-Amino-1H-tetrazole was calcined in air, and after calcination, it was cooled, ball-milled, washed, and dried to obtain nitrogen-rich carbon nitride.

[0006] S2: After mixing nitrogen-rich carbon nitride and acidic solution evenly, stir and heat in an oil bath at a certain temperature, cool, wash and dry to obtain oxygen-doped nitrogen-rich carbon nitride.

[0007] S3: After uniformly mixing alcohol, deionized water and oxygen-doped nitrogen-rich carbon nitride, ultrasonically exfoliate at room temperature for 12-24 hours; wash and dry to obtain nanoscale oxygen-doped nitrogen-rich carbon nitride.

[0008] In S1, the calcination temperature is 400-600℃, the heating rate during calcination is 2-6℃ / min, and the calcination time is 3-5h; the ball milling frequency is 25-45Hz, and the ball milling time is 0.5-1h.

[0009] In S2, after the nitrogen-rich carbon nitride and the acidic solution are mixed evenly, the concentration of the nitrogen-rich carbon nitride is 20 g / L.

[0010] The acidic solution is a diluted sulfuric acid or hydrochloric acid solution. When diluting, the volume ratio of concentrated sulfuric acid or concentrated hydrochloric acid to water is 1:5.

[0011] The oil bath temperature is 90-120℃, and the stirring and heating time is 4-7 hours.

[0012] In S3, the alcohol is an ethanol or ethylene glycol solution, and the volume ratio of alcohol to deionized water is 1:8.

[0013] After the alcohol, deionized water and oxygen-doped nitrogen-rich carbon nitride were mixed evenly, the concentration of oxygen-doped nitrogen-rich carbon nitride was 1 g / L.

[0014] In steps S1-S3, the washing process involves adding deionized water followed by vacuum filtration separation, repeated 2-4 times.

[0015] In steps S1-S3, the drying conditions are: drying temperature of 60-80℃ and drying time of 10-15h.

[0016] The preparation method of the present invention is carried out under solution thermal conditions, and the crystallinity is improved by adjusting the structural characteristics of carbon nitride; at the same time, due to the ultrasonic exfoliation, it is beneficial to form a nanoscale oxygen-doped nitrogen-rich carbon nitride framework structure.

[0017] The present invention also provides a nanoscale oxygen-doped nitrogen-rich carbon nitride, which is prepared according to the above preparation method, and the thickness of the obtained nanoscale oxygen-doped nitrogen-rich carbon nitride is <2nm.

[0018] The present invention also provides the application of the above-mentioned nanoscale oxygen-doped nitrogen-rich carbon nitride in the photocatalytic production of hydrogen peroxide.

[0019] The beneficial effects of this invention are as follows:

[0020] (1) The preparation method of nanoscale oxygen-doped nitrogen-rich carbon nitride of the present invention is simple, the raw materials are widely available and inexpensive, and the finished material is a solid powder that is non-toxic and harmless, easy to separate from water, and is beneficial to practical application.

[0021] (2) The nanoscale oxygen-doped nitrogen-rich carbon nitride of the present invention has a smaller interlayer distance, a larger surface area and more active sites, wherein the thickness is <2nm, which improves the charge transfer efficiency and has better photocatalytic performance.

[0022] (3) The nanoscale oxygen-doped nitrogen-rich carbon nitride of the present invention can efficiently produce hydrogen peroxide, with a photocatalytic hydrogen peroxide yield of up to 346.15 μmol / g. It can be used stably at different temperatures and maintains efficient hydrogen peroxide production performance, and has good photocatalytic stability. Attached Figure Description

[0023] Figure 1 Transmission electron microscope images of nitrogen-rich carbon nitride, oxygen-doped nitrogen-rich carbon nitride, and nanoscale oxygen-doped nitrogen-rich carbon nitride photocatalytic materials; where a is nitrogen-rich carbon nitride, b is oxygen-doped nitrogen-rich carbon nitride, and c is nanoscale oxygen-doped nitrogen-rich carbon nitride.

[0024] Figure 2 This is an atomic force microscope image of the nanoscale oxygen-doped nitrogen-rich carbon nitride photocatalyst material of Example 1;

[0025] Figure 3 X-ray diffraction patterns of nitrogen-rich carbon nitride, oxygen-doped nitrogen-rich carbon nitride, and nanoscale oxygen-doped nitrogen-rich carbon nitride photocatalytic materials;

[0026] Figure 4 Photocatalytic hydrogen peroxide production performance test diagrams for nitrogen-rich carbon nitride, oxygen-doped nitrogen-rich carbon nitride, and nanoscale oxygen-doped nitrogen-rich carbon nitride photocatalytic materials. Detailed Implementation

[0027] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of this application. Unless otherwise specified, all data range values ​​described in this application should include end values.

[0028] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0029] Example 1

[0030] The preparation method of nanoscale oxygen-doped nitrogen-rich carbon nitride in this embodiment includes the following steps:

[0031] S1: Preparation of nitrogen-rich carbon nitride

[0032] Weigh 8g of 5-amino-1H-tetrazole and place it in a ceramic crucible. Calcinate it in a tube furnace at 400℃ for 4h under air atmosphere. The heating rate during calcination is 3℃ / min. After calcination, cool to room temperature and remove to obtain a pale yellow solid. Ball mill the solid and wash it repeatedly with deionized water three times. After each washing, filter the solid under reduced pressure and collect it. Place the solid in a vacuum drying oven at 60℃ and dry for 12h to obtain a pale yellow nitrogen-rich carbon nitride.

[0033] S2: Preparation of oxygen-doped nitrogen-rich carbon nitride

[0034] Concentrated sulfuric acid and deionized water were mixed evenly at a volume ratio of 1:5 to obtain an acidic solution. Then, 5g of nitrogen-rich carbon nitride obtained in step S1 was added. The mixture was stirred and heated in an oil bath at 100℃ for 4 hours. After cooling to room temperature, the solid was washed three times with deionized water. After each washing, the solid was collected by vacuum filtration under reduced pressure and dried in a vacuum drying oven at 60℃ for 12 hours to obtain oxygen-doped nitrogen-rich carbon nitride.

[0035] S3: Preparation of nanoscale oxygen-doped nitrogen-rich carbon nitride

[0036] Weigh 1g of oxygen-doped nitrogen-rich carbon nitride obtained in step S2, mix it evenly with a solution of ethanol and deionized water in a ratio of 1:8, perform ultrasonic exfoliation for 12h, cool to room temperature, wash repeatedly with deionized water three times, collect the solid by vacuum filtration after each washing, place it in a vacuum drying oven at 60℃ for 12h and take it out to obtain nano-scale oxygen-doped nitrogen-rich carbon nitride.

[0037] The morphology, structure, light absorption properties, and photocatalytic activity of nitrogen-rich carbon nitride, oxygen-doped nitrogen-rich carbon nitride, and nanoscale oxygen-doped nitrogen-rich carbon nitride from Example 1 were studied using transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and ultraviolet-visible diffuse reflectance spectroscopy. The photocatalytic hydrogen peroxide production performance was tested using the following methods:

[0038] 10 mg of nitrogen-rich carbon nitride, oxygen-doped nitrogen-rich carbon nitride, and nano-sized oxygen-doped nitrogen-rich carbon nitride photocatalysts were dispersed in 100 mL of aqueous solution, respectively. The solutions were ultrasonicated for 10 min and stirred for 10 min to reach adsorption-desorption equilibrium, saturating the suspensions. The reactions were then irradiated with a 300 W xenon lamp at room temperature under a pressure of 1 standard atmosphere. Samples were taken at specified time intervals, and the supernatant was used for hydrogen peroxide detection. The concentration of hydrogen peroxide was determined using UV-Vis spectrophotometry, with potassium iodide and ammonium molybdate tetrahydrate as the colorimetric reagents, and a maximum absorption wavelength of 352 nm.

[0039] Figure 1 Transmission electron microscope images of nitrogen-rich carbon nitride, oxygen-doped nitrogen-rich carbon nitride, and nanoscale oxygen-doped nitrogen-rich carbon nitride photocatalytic materials. Figure 1The results showed that nitrogen-rich carbon nitride exhibits a typical irregular layered structure. Figure 1 (a) while oxygen-doped nitrogen-rich carbon nitride exhibits an etched nanosheet structure ( Figure 1 (b) Nanoscale oxygen-doped nitrogen-rich carbon nitride exhibits a porous nanosheet structure, significantly increasing its surface area, exposing active sites, and enhancing photocatalytic reactions. Figure 1 (c).

[0040] Figure 2 The AFM thickness map shows a nanoscale oxygen-doped nitrogen-rich carbon nitride photocatalyst with a thickness of 1.6 nanometers.

[0041] Figure 3 X-ray diffraction patterns of nitrogen-rich carbon nitride, oxygen-doped nitrogen-rich carbon nitride, and nanoscale oxygen-doped nitrogen-rich carbon nitride photocatalytic materials are shown. Nitrogen-rich carbon nitride exhibits two typical X-ray diffraction peaks at 13.1° and 27.54°, representing the (100) and (002) crystal planes of carbon nitride, respectively, attributed to the in-plane heptaazine unit structure and interlayer stacking structure. Compared to nitrogen-rich carbon nitride, the peak intensities of the (100) and (002) crystal planes of oxygen-doped and nanoscale oxygen-doped nitrogen-rich carbon nitride decrease and shift towards higher angles, indicating a reduction in interlayer spacing.

[0042] Figure 4 The photocatalytic hydrogen peroxide production performance of nitrogen-rich carbon nitride, oxygen-doped nitrogen-rich carbon nitride, and nanoscale oxygen-doped nitrogen-rich carbon nitride photocatalysts is shown in the graphs. The photocatalytic activities of these three materials were compared by testing their hydrogen peroxide production performance over 80 minutes. The results show that in the 60-minute hydrogen peroxide production, the photocatalytic hydrogen peroxide production rate of nanoscale oxygen-doped nitrogen-rich carbon nitride was approximately 4 times and 11 times that of nitrogen-rich carbon nitride and oxygen-doped nitrogen-rich carbon nitride, respectively, indicating that oxygen doping in the nitrogen-rich carbon nitride framework can significantly improve photocatalytic efficiency.

[0043] Example 2

[0044] The preparation method of nanoscale oxygen-doped nitrogen-rich carbon nitride in this embodiment includes the following steps:

[0045] S1: Preparation of nitrogen-rich carbon nitride

[0046] Weigh 8g of 5-amino-1H-tetrazole and place it in a ceramic crucible. Calcinate it in a tube furnace at 500℃ for 4h under air atmosphere. The heating rate during calcination is 5℃ / min. After calcination, cool to room temperature and remove to obtain a pale yellow solid. Ball mill the solid and wash it repeatedly with deionized water three times. After each washing, filter the solid under reduced pressure and collect it. Place the solid in a vacuum drying oven at 60℃ and dry for 12h to obtain a pale yellow nitrogen-rich carbon nitride.

[0047] S2: Preparation of oxygen-doped nitrogen-rich carbon nitride

[0048] Concentrated sulfuric acid and deionized water were mixed evenly at a volume ratio of 1:5 to obtain an acidic solution. Then, 5g of nitrogen-rich carbon nitride obtained in step S1 was added. The mixture was stirred and heated in an oil bath at 100℃ for 4 hours. After cooling to room temperature, the solid was washed three times with deionized water. After each washing, the solid was collected by vacuum filtration under reduced pressure and dried in a vacuum drying oven at 60℃ for 12 hours to obtain oxygen-doped nitrogen-rich carbon nitride.

[0049] S3: Preparation of nanoscale oxygen-doped nitrogen-rich carbon nitride

[0050] Weigh 1g of oxygen-doped nitrogen-rich carbon nitride obtained in step S2, mix it evenly with a solution of ethanol and deionized water in a ratio of 1:8, perform ultrasonic exfoliation for 12h, cool to room temperature, wash repeatedly with deionized water three times, collect the solid by vacuum filtration after each washing, place it in a vacuum drying oven at 60℃ for 12h and take it out to obtain nanoscale oxygen-doped nitrogen-rich carbon nitride.

[0051] Example 3

[0052] The preparation method of nanoscale oxygen-doped nitrogen-rich carbon nitride in this embodiment includes the following steps:

[0053] S1: Preparation of nitrogen-rich carbon nitride

[0054] Weigh 8g of 5-amino-1H-tetrazole and place it in a ceramic crucible. Calcinate it in a tube furnace at 500℃ for 4h under air atmosphere. The heating rate during calcination is 5℃ / min. After calcination, cool to room temperature and remove to obtain a pale yellow solid. Ball mill the solid and wash it repeatedly with deionized water three times. After each washing, filter the solid under reduced pressure and collect it. Place the solid in a vacuum drying oven at 60℃ and dry for 12h to obtain a pale yellow nitrogen-rich carbon nitride.

[0055] S2: Preparation of oxygen-doped nitrogen-rich carbon nitride

[0056] Concentrated hydrochloric acid and deionized water were mixed evenly at a volume ratio of 1:5 to obtain an acidic solution. Then, 5g of nitrogen-rich carbon nitride obtained in step S1 was added. The mixture was stirred and heated in an oil bath at 100℃ for 4 hours. After cooling to room temperature, the solid was washed three times with deionized water. After each washing, the solid was collected by vacuum filtration under reduced pressure and dried in a vacuum drying oven at 60℃ for 12 hours to obtain oxygen-doped nitrogen-rich carbon nitride.

[0057] S3: Preparation of nanoscale oxygen-doped nitrogen-rich carbon nitride

[0058] Weigh 1g of oxygen-doped nitrogen-rich carbon nitride obtained in step S2, mix it evenly with a solution of ethanol and deionized water in a ratio of 1:8, perform ultrasonic exfoliation for 12h, cool to room temperature, wash repeatedly with deionized water three times, collect the solid by vacuum filtration after each washing, place it in a vacuum drying oven at 60℃ for 12h and take it out to obtain nanoscale oxygen-doped nitrogen-rich carbon nitride.

[0059] Example 4

[0060] The preparation method of nanoscale oxygen-doped nitrogen-rich carbon nitride in this embodiment includes the following steps:

[0061] S1: Preparation of nitrogen-rich carbon nitride

[0062] Weigh 8g of 5-amino-1H-tetrazole and place it in a ceramic crucible. Calcinate it in a tube furnace at 500℃ for 4h under air atmosphere. The heating rate during calcination is 5℃ / min. After calcination, cool to room temperature and remove to obtain a pale yellow solid. Ball mill the solid and wash it repeatedly with deionized water three times. After each washing, filter the solid under reduced pressure and collect it. Place the solid in a vacuum drying oven at 60℃ and dry for 12h to obtain a pale yellow nitrogen-rich carbon nitride.

[0063] S2: Preparation of oxygen-doped nitrogen-rich carbon nitride

[0064] Concentrated sulfuric acid and deionized water were mixed evenly at a volume ratio of 1:5 to obtain an acidic solution. Then, 5g of nitrogen-rich carbon nitride obtained in step S1 was added. The mixture was stirred and heated in an oil bath at 100℃ for 4 hours. After cooling to room temperature, the solid was washed three times with deionized water. After each washing, the solid was collected by vacuum filtration under reduced pressure and dried in a vacuum drying oven at 60℃ for 12 hours to obtain oxygen-doped nitrogen-rich carbon nitride.

[0065] S3: Preparation of nanoscale oxygen-doped nitrogen-rich carbon nitride

[0066] Weigh 1g of oxygen-doped nitrogen-rich carbon nitride obtained in step S2, mix it evenly with a solution of ethylene glycol and deionized water in a ratio of 1:8, perform ultrasonic exfoliation for 12h, cool to room temperature, wash repeatedly with deionized water three times, collect the solid by vacuum filtration after each washing, place it in a vacuum drying oven at 60℃ for 12h and take it out to obtain nano-scale oxygen-doped nitrogen-rich carbon nitride.

[0067] Example 5

[0068] The preparation method of nanoscale oxygen-doped nitrogen-rich carbon nitride in this embodiment includes the following steps:

[0069] S1: Preparation of nitrogen-rich carbon nitride

[0070] Weigh 8g of 5-amino-1H-tetrazole and place it in a ceramic crucible. Calcinate it in a tube furnace at 500℃ for 4h under air atmosphere. The heating rate during calcination is 5℃ / min. After calcination, cool to room temperature and remove to obtain a pale yellow solid. Ball mill the solid and wash it repeatedly with deionized water three times. After each washing, filter the solid under reduced pressure and collect it. Place the solid in a vacuum drying oven at 60℃ and dry for 12h to obtain a pale yellow nitrogen-rich carbon nitride.

[0071] S2: Preparation of oxygen-doped nitrogen-rich carbon nitride

[0072] Concentrated hydrochloric acid and deionized water were mixed evenly at a volume ratio of 1:5 to obtain an acidic solution. Then, 5g of nitrogen-rich carbon nitride obtained in step S1 was added. The mixture was stirred and heated in an oil bath at 100℃ for 4 hours. After cooling to room temperature, the solid was washed three times with deionized water. After each washing, the solid was collected by vacuum filtration under reduced pressure and dried in a vacuum drying oven at 60℃ for 12 hours to obtain oxygen-doped nitrogen-rich carbon nitride.

[0073] S3: Preparation of nanoscale oxygen-doped nitrogen-rich carbon nitride

[0074] Weigh 1g of oxygen-doped nitrogen-rich carbon nitride obtained in step S2, mix it evenly with a solution of ethylene glycol and deionized water in a ratio of 1:8, perform ultrasonic exfoliation for 12h, cool to room temperature, wash repeatedly with deionized water three times, collect the solid by vacuum filtration after each washing, place it in a vacuum drying oven at 60℃ for 12h and take it out to obtain nano-scale oxygen-doped nitrogen-rich carbon nitride.

[0075] The embodiments described above are preferred embodiments of the present invention, but the present invention is not limited to the above embodiments, nor is it limited thereto. Any obvious improvements, substitutions, or modifications that can be made by those skilled in the art without departing from the essence of the present invention are within the protection scope of the present invention.

Claims

1. A method for preparing nanoscale oxygen-doped nitrogen-rich carbon nitride, characterized in that, Includes the following steps: S1: 5-Amino-1H-tetrazole was calcined in air, and after calcination, it was cooled, ball-milled, washed, and dried to obtain nitrogen-rich carbon nitride; the calcination temperature was 400-600℃, and the calcination time was 3-5h; S2: After uniformly mixing nitrogen-rich carbon nitride and acidic solution, stir and heat in an oil bath at 90-120℃ for 4-7 hours, cool, wash, and dry to obtain oxygen-doped nitrogen-rich carbon nitride; wherein, after uniformly mixing nitrogen-rich carbon nitride and acidic solution, the concentration of nitrogen-rich carbon nitride is 20 g / L; the acidic solution is diluted sulfuric acid or hydrochloric acid solution, and the volume ratio of concentrated sulfuric acid or concentrated hydrochloric acid to water is 1:5 during dilution; S3: After uniformly mixing alcohol, deionized water and oxygen-doped nitrogen-rich carbon nitride, ultrasonically exfoliate at room temperature for 12-24 hours, wash and dry to obtain nanoscale oxygen-doped nitrogen-rich carbon nitride; wherein, after uniformly mixing alcohol, deionized water and oxygen-doped nitrogen-rich carbon nitride, the concentration of oxygen-doped nitrogen-rich carbon nitride is 1 g / L; the alcohol is ethanol or ethylene glycol, and the volume ratio of alcohol to deionized water is 1:

8.

2. The preparation method according to claim 1, characterized in that, In S1, the heating rate during calcination is 2-6℃ / min.

3. The preparation method according to claim 1, characterized in that, In S1, the ball milling frequency is 25-45Hz, and the ball milling time is 0.5-1h.

4. The preparation method according to claim 1, characterized in that, In steps S1-S3, the washing process involves adding deionized water followed by vacuum filtration separation, repeated 2-4 times.

5. The preparation method according to claim 1, characterized in that, In steps S1-S3, the drying conditions are: drying temperature of 60-80℃ and drying time of 10-15h.

6. A nanoscale oxygen-doped nitrogen-rich carbon nitride, characterized in that, It is obtained by the preparation method described in any one of claims 1 to 5, and has a thickness of <2nm.

7. The use of the nanoscale oxygen-doped nitrogen-rich carbon nitride as described in claim 6 for photocatalytic production of hydrogen peroxide.

Citation Information

Patent Citations

  • Nitrogen-rich carbon nitride nanosheet and preparation method thereof

    CN111573637A